Women's contraceptive practices and sexual behaviour in Europe - Cibula, David (The European journal of contraception & reproductive health care, 2008)
OBJECTIVES: To assess current and past contraceptive usage, awareness of and satisfaction with available methods, and sexual and reproductive behaviour of women in 14 European countries (Spain, Italy, UK, France, Germany, Sweden, Denmark, Norway, the Czech Republic, Austria, Estonia, Latvia, Lithuania, and the Russian Federation). METHODS: A random sample of women aged 15-49 years underwent web-based or computer-aided face-to-face interviews in June 2006. All data were weighted to correct for differences between the samples surveyed in each country relative to their general population, and further weighted relative to the size of the overall female population across the participating countries. RESULTS: A total of 11,490 women participated in the study. The mean age at first sexual intercourse ranged between 16.5 and 18.5 years. The use of contraception at first intercourse varied significantly across Europe - the rates were the highest in Germany (76%) and France (72%), and the lowest in Russia, the Czech Republic and the Baltic States (29-40%). There was considerable heterogeneity in the general pattern of current contraceptive usage between countries. Oral contraceptives were the most popular current method of contraception, with usage rates highest in France (49%) and the Czech Republic (44%) and lowest in Russia, the Baltic States and Spain (15-18%). The current absence of contraception was fairly consistent across countries, ranging from 21-30%. However, Russia (57%) and the Baltic States (50%) had the highest proportion of women using either no contraception or 'other methods' (mostly methods considered unreliable). CONCLUSIONS: Oral contraceptives remain a popular method of contraception in Europe; however, great differences exist in contraception acceptance and in the rates of use of the various methods. A sizeable proportion of women do not currently use contraception or use contraceptive methods considered to be unreliable.
Keywords: Patient Satisfaction; Humans; Sexual Behavior; lidé středního věku; socioekonomické faktory; Female; Cross-Cultural Comparison; mladý dospělý; dospělí; srovnání kultur; lidé; antikoncepční chování; Europe; spokojenost pacientů; Socioeconomic Factors; Adult; Contraception Behavior; ženské pohlaví; Middle Aged; Adolescent; Young Adult; Evropa; sexuální chování; mladiství; uvědomování si; Awareness